Current and future applications of the anti-IgE antibody omalizumab - Cristoforo Incorvaia (Dove Medical Press, 2008)
Cristoforo Incorvaia1, Marina Mauro2, Gian Galeazzo Riario-Sforza1,Franco Frati3, Francesco Tarantini4, Maurizio Caserini41Allergy/Pulmonary rehabilitation, ICP Hospital, Milan, Italy; 2Allergy Unit, Sant’Anna Hospital, Como, Italy; 3University Department of Obstetric, Gynaecologic and Pediatric Sciences, Perugia, Italy; 4Respiratory Clinical Research, Novartis Farma S.p.A., Origgio, ItalyAbstract: IgE antibodies are a pivotal factor in pathophysiology of allergic diseases, and the possibility of reducing their level by anti-IgE has long been envisioned. Following several attempts, an effective biologic agent was obtained with the recombinant humanized monoclonal antibody (rhuMAb)-E25, known as omalizumab. A number of controlled clinical trials demonstrated its efficacy and safety in the treatment of severe allergic asthma uncontrolled by standard drug treatment with maximal recommended doses, and treatment with omalizumab is currently included in international guidelines on asthma management. Other studies reported a clear effectiveness also in allergic rhinitis, but the cost of the anti-IgE treatment suggests its use in patients with rhinitis concomitant with asthma. Other indications to be further investigated are skin disorders such as atopic dermatitis and IgE-mediated urticaria, as well as adverse reactions to foods, with a particularly important role in preventing food-induced anaphylaxis. Finally, there are data indicating the usefulness of omalizumab when used in combination with allergen specific immunotherapy, in terms of reducing the adverse reactions to treatment and increasing the clinical efficacy.Keywords: IgE, anti-IgE, omalizumab, allergic asthma, allergic rhinitis, atopic dermatitis, food allergy, allergen immunotherapy